Vergeben und Vergessen? Amnestie in der Antike - Harter-Uibopuu, Kaja (2013)
Amnesty as an institutionally imposed act of „Forgiving and Forgetting“ is nowadays practised in various fields. Whether it is granted due to security, domestic or financial policy reasons, the freedom and escape from punishment are always in stark contrast to the individual’s compelling responsibility as the basis of our judicial system as well as to the demand for retribution and social peace. This legal institute is not only terminologically harking back to ancient times but also technically. Similar measures are attested throughout the whole of antiquity.